Flotation of chalcopyrite in water containing bacteria - Liu, W.; Moran, Chris; Vink, S. (2012)
The use of multiple sources of water supply and introducing water reuse in mineral processing have been part of the operating philosophy for the minerals industry to save freshwater and reduce mine water discharge. A consequence of implementing these practices is that water quality can be compromised, which in turn can impact flotation performance. A number of studies have shown that dissolved abiotic watet constituents can have different effects on flotation performance depending on the operating conditions and reagent regimes. However, far less is known about the impacts and processes associated with biotic water constituents, including microorganisms. In this study, we investigated the effect of bacteria (E. coli) on mineral (chalcopyrite) flotation performance using both microflotation and scale-up batch flotation tests. Microflotation results indicated that the presence of E. coli in water had an adverse effect on the flotation of chalcopyrite. The magnitude of the adverse effect increased with the increase of bacterial cell concentration. The adverse effect could be mitigated to different extents by increasing the collector concentration depending on the bacterial cell concentration. The adverse effect was also observed in batch flotation tests. Froth images taken showed that the bubble size and bubble load were affected by the presence of the bacteria.